PVT1 Long Non-coding RNA in Gastrointestinal Cancer - Martinez-Barriocanal, Agueda; Arango, Diego; Dopeso, Higinio (Frontiers in Oncology, 2020)
Whole genome and transcriptome sequencing technologies have led to the identification of many long non-coding RNAs (lncRNAs) and stimulated the research of their role in health and disease. LncRNAs participate in the regulation of critical signaling pathways including cell growth, motility, apoptosis and differentiation; and their expression has been found dysregulated in human tumors. Thus, lncRNAs have emerged as new players in the initiation, maintenance and progression of tumorigenesis. PVT1 (plasmacytoma variant translocation 1) lncRNA is located on chromosomal 8q24.21, a large locus frequently amplified in human cancers and predictive of increased cancer risk in genome-wide association studies (GWAS). Combined, colorectal and gastric adenocarcinomas are the most frequent tumor malignancies and also the leading cause of cancer-related deaths worldwide. PVT1 expression is elevated in gastrointestinal tumors and correlates with poor patient prognosis. In this review, we discuss the mechanisms of action underlying PVT1 oncogenic role in colorectal and gastric cancer such as MYC upregulation, miRNA production, competitive endogenous RNA (ceRNA) function, protein stabilization and epigenetic regulation. We also illustrate the potential role of PVT1 as prognostic biomarker and its relationship with resistance to current chemotherapeutic treatments.